Effect Of Artificial Enhancement On Biodiversity In Marine Concrete-Based Structures - Yee, Jean Chai (2021)
Marine concrete-based structures such as seawalls, breakwaters and revetments are progressively built followed by intensified coastal development activities. However, these structures often have low ecological values due to low structural complexity. In the present study, a novel technique of ecological engineering was used to improve the structural complexity of existing seawalls to promote the growth of native biodiversity and potentially rehabilitate ecological function of marine concretebased structures.